Play to Liberate: Integrasi Games Based Learning sebagai Wujud Pembelajaran Reflektif dan Upaya Mewujudkan Pendidikan Pembebasan di Era Digital - Vanriel, Melki; Yovi, Andrias (Universitas Muhammadiyah Magelang, 2026)
This study aims to examine the integration of Game-Based Learning (GBL) as a form of reflective learning in the effort to realize emancipatory education within a digital context, taking as its point of departure the strong dominance of transmissive instructional practices that continue to constrain student agency and critical dialogic engagement. The research adopts a qualitative approach with a case study design. Data were collected through semi-structured interviews, participatory observation, and the analysis of instructional documents involving teachers and students engaged in the implementation of GBL, with participants selected through purposive sampling. Thematic analysis reveals three principal findings: a shift in students’ roles toward becoming active learning subjects, the development of reflective practices grounded in gameplay experiences, and the emergence of spaces for critical dialogue that foster the growth of social awareness in the classroom. These findings affirm the capacity of GBL as a reflective pedagogical medium oriented toward emancipation. In terms of implications, they highlight the necessity of designing GBL with systematically structured phases of reflection, while further research is recommended to explore cross-level applications and long-term impacts.